Tunable blue-green emitting and energy transfer of a Eu2+/Tb3+ codoped Sr3La(PO4)3 phosphor for near-UV white LEDs. (18th September 2015) - Bai, Qiongyu; Wang, Zhijun; Li, Panlai; Xu, Shuchao; Li, Ting; Yang, Zhiping
Abstract : A series of Eu 2+ and Tb 3+ doped Sr3 La(PO4 )3 phosphors have been synthesized via the high-temperature solid-state reaction method. Abstract : A series of Eu 2+ and Tb 3+ doped Sr3 La(PO4 )3 phosphors have been synthesized via the high-temperature solid-state reaction method. X-ray diffraction (XRD) patterns, luminescence spectra including temperature-dependent luminescence spectra, and fluorescence decay lifetimes have been used to characterize the as-prepared samples. Under ultraviolet excitation, Sr3 La(PO4 )3 :Eu 2+ shows a strong blue emission around 418 nm and a shoulder centered at 500 nm, which is based on the substitution of two kinds of Sr 2+ sites by Eu 2+ ions (Eu1 and Eu2). Sr3 La(PO4 )3 :Tb 3+ shows characteristic emission lines of Tb 3+ under 376 nm excitation. For Sr3 La(PO4 )3 :Eu 2+, Tb 3+ phosphor, similar excitation spectra monitored at 418, 500 and 545 nm have been observed, which illustrates the possibility of energy transfer from Eu 2+ to Tb 3+ ions. Compared with the Tb 3+ singly doped phosphor, the codoped phosphors have more intense absorption in the n-UV range and stronger emission of the Tb 3+ ions, which are attributed to the effective energy transfer from the Eu 2+ to Tb 3+ ions. The variations in the emission spectra, emission color and decay lifetimes further demonstrate the existence of energy transfer from Eu 2+ to Tb 3+ ions under ultraviolet excitation. For Eu1 and Eu2, the energy transfer mechanism has been confirmed to be quadrupole–quadrupole and dipole–quadrupole interaction, respectively. The results can be validated via the agreement of critical distances obtained from the concentration quenching (21.62 Å). These results show that the phosphors may possess potential application in ultraviolet-based white light-emitting diodes.